EFFECTS OF CONTINUOUS TRAINING AND DEVELOPMENT ON RAPID RESPONSE UNIT FOR IMPROVING TIME INTERVENTION - Sonya Pebriani; Sugeng Riyanto; Pupung Purnamasari; Allessandro Setyo Anggito Utomo; Mikael Januardi Ginting; Anondho Wijanarko (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2021)
The research conduct a case study on the rapid response unit through a quantitative approach regarding the effect of continuous training and development for in resolving emergencies and developing rapid response system. The Rapid Response Unit (RRU) is a unit that helps avoid the risk of adverse events that threaten the safety of community interaction in the area in the campus forest area. However, the unit's existence is not enough to only present physiques with the available time to help secure and control various of events in the campus forest area. An increase in hard and soft skills is needed to maintain quality of rapid response unit human resource. The study results indicate an impact in resolving incidents based on the time spent of intervention in the crucial level of the incident, the level of familiarity of events for the field officers, and the adequacy of training provided.